Literasi Digital dan Sosialisasi Hukum Pencegahan Game Online Menjadi Judi Online - Ivan Fauzani Raharja; Eko Nuriyatman; Syurpana Nofanda; Ratna Dewi; Melia Rizki Ruswandi (LPPM UNIVERSITAS MUHAMMADIYAH MUARA BUNGO, 2026)
This community service program aims to increase digital literacy and legal understanding of the Jujun Village community to prevent the misuse of online games into online gambling through socialization, educational lectures, and legal training. The problem of online gambling in Indonesia has increased drastically with transactions reaching IDR 327 trillion in 2023, an increase of 213% from the previous year. Jambi Province ranks highest in online gambling users nationally. The low level of digital literacy in Indonesian society, which has only reached 41.48%, is an important factor in vulnerability to online game misuse. The activity methods include interactive legal lectures, socialization on identifying online games with gambling potential, and education on legal consequences based on the ITE Law, Criminal Code, and related regulations. The program involved 50 participants (junior/senior high school students, parents, and village government) with a target of 85% increase in legal understanding. The results showed an increase in legal awareness, understanding of criminal sanctions for online gambling, and commitment to recommend the formation of anti-online gambling village policies. Program outputs include publication of accredited national journal articles, video documentation, and Intellectual Property Rights.